Sulbactam-durlobactam combination therapy for carbapenem-resistant Acinetobacter baumannii sepsis with cutaneous involvement in an infant with acute monocytic leukemia: A case report - Fu, Chunxi; Tang, Xue; Guo, Xia; Huang, Liang; Gao, Ju; Yang, Rong (Frontiers in Pharmacology, 2025)
Carbapenem-resistant Acinetobacter baumannii (CRAb) causes severe infections and poses significant treatment challenges. Sulbactam-durlobactam (SUL-DUR) is a novel antibiotic, but its use in children and infants has not been reported. We reported the first case of an infant with acute leukemia successfully treated with SUL-DUR for CRAb sepsis with cutaneous involvement.